Legal Protection for Teachers Against Threats of Physical Violence from Parents at School - Tatik Ernawati; M. Syahrul Borman; Dedi Wardana Nasoetion; Vallencia Nandya Paramitha; Hartoyo Hartoyo (Journal of International Multidisciplinary Research, 2025)
The teaching profession plays a strategic role in advancing national education, as mandated by the 1945 Constitution of the Republic of Indonesia. However, teachers frequently face challenges, including threats of physical violence from students’ parents, which undermine their dignity and safety in the educational environment. This study addresses the problem of how legal frameworks provide protection for teachers and whether existing regulations adequately ensure their rights and security. The research aims to analyze the effectiveness of legal protection for teachers under the Criminal Code, Law No. 14 of 2005 on Teachers and Lecturers, Law No. 35 of 2014 on Child Protection, and Ministerial Regulations concerning teacher protection. The study employs a normative juridical method with a statute, conceptual, and case approach, relying on primary, secondary, and tertiary legal materials, analyzed through qualitative interpretation and juridical argumentation. The results indicate that although legal instruments exist, their implementation remains weak due to the absence of technical regulations, limited institutional coordination, and insufficient support systems for teachers at the school level. The study concludes that derivative regulations and integrated mechanisms are essential for ensuring effective protection. It recommends strengthening inter-agency coordination, establishing school-level protection units, and enhancing teachers’ legal literacy.